A Challenging case of essensial iris atrophy ICE Syndrome with secondary angle closure glaucoma at Pasar Rebo General Hospital : A Case Report: Poster Presentation - Case Report - General practitioner - Nasrudin; Indrianti, Dayu Fitria; Simanjuntak, Dicky Budiman (Majalah Oftalmologi Indonesia, 2023)
Introduction : ICE syndrome is a unique ophthalmic disorder that involves an iris atrophy, irregular corneal oedema, and secondary angle-closure mainly occurs unilaterally in young and middle-aged women, with no family history. Approximately 50% of ICE syndrome patients will later develop secondary angle closure glaucoma. The following case report presents a patient with essential iris atrophy and secondary angle closure glaucoma. Case Illustration : A 50 year old woman presented with painful and redness of the right eye (RE) since 1 week. Her visual acuity was 6/40 of RE and 6/30 of left eye (LE). Her intraocular pressure (IOP) was 61,3 mmHg and 19 mmHg for the RE and LE. On the slit lamp, we had a proper RE finding, the iris atrophy with deformity in the direction from 12 to 6 hours, with minimal corneal edema. We performed gonioscopy, fundus photographs and papillary optical coherence tomography. The patient was diagnosed with ICE syndrome with essential iris atrophy type and secondary angle closure glaucoma then was given anti glaucoma agents.DiscussionICE syndrome treatments focus on managing the corneal edema and secondary glaucoma. We treated our patient with maximal oral and topical combination therapy such as carbonic anhydrase inhibitors, beta blockers, cholinergic, prostaglandin analogs for 6 months the IOP and corneal oedema were well maintained. However, maintaining long term success can be challenging, surgical therapy with a filtering procedure can be considered if the IOP is uncontrolled. Conclusion : We confirmed the diagnosis of essential iris atrophy based on its clinical findings and abnormalities in complementary exams.